Herschel star-ATLAS/GAMA: the environmental density of far-infrared bright galaxies at z < 0.5 - Burton, C; Jarvis, M; Smith, D; Bonfield, D; Hardcastle, M; Stevens, J; Bourne, N; Baes, M; Brough, S; Cava, A; Cooray, A; Dariush, A; et al. (2013)
We compare the environmental and star formation properties of far-infrared detected and non-far-infrared detected galaxies out to z ~ 0.5. Using optical spectroscopy and photometryfrom the Galaxy And Mass Assembly (GAMA) and Sloan Digital Sky Survey, with farin frared observations from the Herschel Astrophysical Terahertz Large Area Survey (ATLAS)Science Demonstration Phase, we apply the technique of Voronoi tessellations to analyse the environmental densities of individual galaxies. Applying statistical analyses to colour, r-band magnitude and redshift-matched samples, we show that there is a significant differenceat the 3.5σ level between the normalized environmental densities of these two populations. This is such that infrared emission (a tracer of star formation activity) favours underden seregions compared to those inhabited by exclusively optically observed galaxies selected to beof the same r-band magnitude, colour and redshift. Thus, more highly star-forming galaxiesare found to reside in the most underdense environments, confirming previous studies thathave proposed such a correlation. However, the degeneracy between redshift and far-infraredluminosity in our flux-density-limited sample means that we are unable to make a strongerstatement in this respect. We then apply our method to synthetic light cones generated fromsemi-analytic models, finding that over the whole redshift distribution the same correlations between star formation rate and environmental density are found. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.